Political Change and Reform to the Budgetary System in Mexico (Andamios, Revista de Investigación Social, 2013)
This article argues that the 2004 reform of the constitutional framework of the Mexican budgetary system and the quest for new power among the political actors in the context of political change are the keys to understand the new institutional and political frame for the approval of the federal budget in Mexico. It also proposes that the Mexican federal budget has acquired a distributive profile under last minority governments, and that its legislative approval has also became an opportunity for political struggle for power.
Keywords: Budget; Mexico’s Budgetary System; Institutional Reform; Political Change; Re-allocation of Power